Characterising the slope of the distance-time relationship in swimming - Dekerle, J.; Brickley, G.; Alberty, M.; Pelayo, P. (Journal of Science and Medicine in Sport, 2010)
The aim of the present study was to assess whether the critical speed calculated by the slope of the distance-time relationship (Sd-t) represents the boundary between the heavy and severe intensity domains in swimming and would be sustainable during intermittent exercise. Nine competitive male swimmers (mean ± SD: aged 21.2 ± 2.6 yrs; peak VO2 of 3866 ± 529 mL min-1) performed, (a) four fixed-distance (100-200-400-800 m) all-out efforts to determine Sd-t and peak VO2 ; (b) three constant-speed efforts to exhaustion (TTE) at and 5% above and below Sd-t ; (c) a set of 10 × 400 m at Sd-t with 40-s recovery in between. Capillary blood lactate concentration ([La]B), oxygen uptake, and RPE remained stable at VO2 (TTE = 48.9 ± 14.1 min) with end values of 3.8 ± 1.9 mmol L-1, 87 ± 14% peak VO2, and 4.7 ± 1.3. TTE decreased at VO2 (8.6 ± 3.1 min), with end [La]B of 10.2 ± 1.9 mmol L-1. Peak VO2 was reached at exhaustion. Similarly, Sd-t could only be maintained for 24.3 ± 7.7 min with an increase in RPE and [La]B, VO2 reaching its peak (95 ± 5% peak VO2 ). RPE increased but [La]B remained stable throughout the ten 400 m blocks performed at Sd-t (overall time of 53.9 ± 2.7 min). The physiological responses when swimming 5% below and 5% above Sd-t are those characterising the heavy and severe intensity domain, respectively. While Sd-t lies within the severe intensity domain, intermittent swims at this intensity induce [La]B steady state alongside high rates of perceived exertion.